Atlantis Restored: Natural Knowledge and Political Economy in Early Modern Sweden. - Wennerlind, Carl (American Historical Review, 2022)
After success in the Thirty Years' War, elites in Sweden realized that the nation had to establish a new economic base to support its newfound geopolitical prominence. Drawing on the Pan-European natural-knowledge-based political economy, Swedish reformers developed a version uniquely applicable to the nation's challenges and opportunities. At the center of this new political economy was the use of scientific knowledge to transform nature into usable wealth. Whether physics, alchemy, mechanics, or botany, any form of knowledge with the power to transform nature through mining, agriculture, or manufacturing was considered valuable. Drawing on either Paracelsian spiritual ideas or those of Cartesian materialism, Swedish improvement thinkers sought to penetrate deep into the inner life of nature and thereby unlock the storehouse of wealth that God had placed therein. This article traces how Johan Risingh, Urban Hiärne, Christopher Polhem, and Carl Linnaeus, in conversation with foreign improvers, combined knowledge of the natural world with commercial considerations to form a discourse they hoped would enable Sweden to embark on a trajectory of economic growth and thereby restore its mythical glory as the cradle of European civilization.